Angiogenesis Intensity within Benign and Malignant Oral Mucosa Epithelial Tumor - Sudiono, Janti; Thalib, Sofia (Molecular and Cellular Biomedical Sciences, 2018)
Background: Angiogenesis is an important and fundamental process for new blood vessels to provide nutrients and oxygen needed by tumor cells to grow, develop, and in case of cancer also to metastasize into other organs. This study aims to evaluate the intensity of angiogenesis within benign (papillomas) and malignant (squamous cell carcinoma) epithelial tumors.Materials and methods:  This analytic observational study with cross-sectional design using histopathology slide sample that were clinically diagnosed as squamous cell carcinoma (n=3) and papilloma (n=3). Microscopically, the angiogenesis characterized with lumen lined by endothelial cells with or without red blood cells inside within sub epithelial connective tissue of papilloma and squamous cell carcinoma by Hematoxylin Eosin stain. Angiogenesis intensity was counted from four areas under magnification of (10x10), each area was scored under (10x40) magnification.Results: Angiogenesis intensity of papilloma and squamous cell carcinoma are (45.17±14.573) and (55.18±6.26041) respectively. T-test analysis showed there was no significant difference (p=0.336>0.05).Conclusions: Angiogenesis intensity of papilloma is less than those of squamous cell carcinoma.Keywords: angiogenesis, oral epithelial tumor, benign, malignant